Desenvolvimento de Amplificadores de RF baseado em Fot?nica para Redes 5G - Noque, Dion?sio Fama (2017)
This working is regarding the development and characterization of a photonics-based radiofrequency (RF) amplifier, entitled PBRA. It takes advantage of the Four-wave Mixing nonlinear (FWM) effect, with the aim of providing RF gain for the fifth generation of cellular networks (5G) based on optical backhauls. The FWM effect is intensified by the use of a Highly Nonlinear Fiber (HNLF) with nonlinear coefficient ? = 28 W-1km-1. The RF gain is defined as the electrical power difference between the FWM product and conventional Radio over Fiber (RoF) system at the photodetector output. Experimental results demonstrate the PBRA applicability for the 5G potential frequency bands, such as 6, 28 and 38 GHz. A 27-dB gain has been obtained over an ultrawide range from 300 kHz to 50 GHz, besides linearity improvement compared to the conventional RoF system. Analyses of electrical and optical parameters, such as optical power, laser pump spacing, RF gain, signal-to-noise ratio, phase noise, Spurious-Free Dynamic Range (SFDR), noise figure and Error Vector Magnitude (EVM), have been exploited for the PBRA validation. Finally, an experimental thermal investigation from -10 to + 70?C of the amplifier operation has been carried out for validating its use under real conditions.